(untitled) (Ius Novum, 2020)
A notary is liable for harm inflicted in the course of a notarial transaction whether on a client or third parties, on the basis of Article 415 of the Civil Code, on account of failure to exercise due diligence (Article 49 Notarial Law Act), in a culpable manner, subject to the professional nature of the notary’s activities (Article 355 § 2 Civil Code) and the limits of professional diligence set out by Article 80 § 1 to § 3 NLA. The notary is the bearer of an office of public trust, and documents containing notarial transactions are official documents within the meaning of the Code of Civil Procedure. The notary’s task is to guarantee the safety and credibility of legal transactions, which is of importance both to the public interest and the private interests of parties to notarial transactions. The proceedings before the notary are not a contest between the parties, and the nature of control exercised by the notary is preventive.